2021
DOI: 10.3389/fimmu.2021.749264
|View full text |Cite
|
Sign up to set email alerts
|

Diphtheria And Tetanus Vaccination History Is Associated With Lower Odds of COVID-19 Hospitalization

Abstract: BackgroundCOVID-19 is characterized by strikingly large, mostly unexplained, interindividual variation in symptom severity: while some individuals remain nearly asymptomatic, others suffer from severe respiratory failure. Previous vaccinations for other pathogens, in particular tetanus, may partly explain this variation, possibly by readying the immune system.MethodsWe made use of data on COVID-19 testing from 103,049 participants of the UK Biobank (mean age 71.5 years, 54.2% female), coupled to immunization r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
4
7
0
Order By: Relevance
“…This finding is in consensus with multiple studies which describe cross-reactive immunity from these vaccines as a possible mechanism [6], [17], [18]. A study by Monereo-Sanchez et al reports that patients, who received diphtheria and tetanus vaccines were less likely to develop severe COVID-19 infection [6]. A molecular-level analysis was done by Reche et al, which found that there was significant cross-reactivity between diphtheria, tetanus and pertussis combination vaccine [17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is in consensus with multiple studies which describe cross-reactive immunity from these vaccines as a possible mechanism [6], [17], [18]. A study by Monereo-Sanchez et al reports that patients, who received diphtheria and tetanus vaccines were less likely to develop severe COVID-19 infection [6]. A molecular-level analysis was done by Reche et al, which found that there was significant cross-reactivity between diphtheria, tetanus and pertussis combination vaccine [17].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, it was also found that the percentage of children given DTP immunization showed a negative linear relationship with COVID-19 mortality. This finding is in consensus with multiple studies which describe cross-reactive immunity from these vaccines as a possible mechanism [6], [17], [18]. A study by Monereo-Sanchez et al reports that patients, who received diphtheria and tetanus vaccines were less likely to develop severe COVID-19 infection [6].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Second, children aged 12-23 months who have received DPT and measles immunizations support a number reduction for some COVID-19 related numbers. These findings agreed with previous research that state Diphtheria vaccination history is associated with lower odds of COVID-19 hospitalization thus reduced the number of severe reaction and deaths caused by COVID-19 [14].…”
Section: Percentile Of New Cases Of Covid-19 Per Day (𝒀 𝟓 )supporting
confidence: 93%
“…Interestingly, the re-infections with age did not influence the neutralizing activity although it appeared to increase the cross-reactivity antigen-specific antibodies levels. Nevertheless, other studies have found that vaccination of measles-mumps-rubella or tetanus-diphtheria-pertussis provided a protective role against the severe COVID-19 by activating the cross-reactive T cell response, which is a possible explanation for children with reduced susceptibility and severe clinical syndrome in SARS-CoV-2 infection ( 39 41 ). Thus, the cross-reactive T cell response should be an important point for future study since poor cross-reactive neutralizing antibodies are stimulated by LPH-CoVs.…”
Section: Discussionmentioning
confidence: 99%